PENGARUH BRAND IMAGE DAN PRODUCT INNOVATION TERHADAP CUSTOMER LOYALTY YANG DIMEDIASI OLEH BRAND TRUST PADA PENGGUNA SMART TV SAMSUNG DI BANDUNG RAYA - Wildan Firmansyah; Hariyadi Triwahyu Putra (Universitas Sarjanawiyata Tamansiswa, 2025)
This study aims to analyze the effect of brand image, product innovation on customer loyalty mediated by brand trust on Samsung Smart TV users in Bandung Raya in 2024. The research instrumenthas gone through the stages of validity dan reliability test, classical assumption test, multiple regression test, dan sobel testing. The instrumen is used as a tool for collecting data from respondents who have purchased Samsung Smart TV and are domiciled in Bandung raya which is the object assessed in this study. Collected through a questionnare created using a google form involving 120 respondents selected using convenience sampling techniques and analyzed using SPSS. The result of the hypothesis test show that brand image has a significant positive effect on brand trust and has an insignificant positive effect on customer loyalty. Brand trust affects customer loyalty and mediates the influence of brand image and product innovation on customer loyalty. The result of this study are expected to be useful for managers of similar objects being assessed because they will help create appropriate strategies or programs.